HUMANISASI DALAM PEMBELAJARAN FISIKA HUMANIZATION IN LEARNING PHYSICS - Zose Wirawan; Restu Januarty; Ahmad Yani; M. Agus Martawijaya (Fakultas Keguruan dan Ilmu Pendidikan, 2022)
This research was pre-experimental. This study aimed to determine the achievement of learning outcomes for class X students of SMA Barrang Lompo by applying a humanistic science learning approach that is by students' hobbies and which is not by students' hobbies. The independent variable in this study is the humanistic science learning approach and the dependent variable is the result of learning physics in the cognitive domain. The subjects in this study were two students who each had different hobbies. The cognitive instrument by providing an assessment of the results of measurements carried out as a final test. The descriptive analysis provides conclusions about the achievement of learning outcomes of the research subject students whose hobbies are on the guitar achieve individual mastery with a minimum score of 65 while students whose hobbies are not on the guitar have not achieved individual mastery with a minimum score of 65.